A kind of anti-seepage and anti-freeze concrete composite admixture suitable for high-cold areas and its preparation method

Through the synergistic effect of multiple components of anti-seepage and anti-freeze concrete composite admixture, the problem of single components of existing anti-freeze admixture is solved, significantly improving the freezing resistance and durability of concrete, and is suitable for infrastructure construction in high-altitude areas. .

CN118652069BActive Publication Date: 2025-02-25RIZHAO FEM NEW MATERIAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410843505.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-02-25
Estimated Expiration
2044-06-27

AI Technical Summary

Technical Problem

The existing anti-freeze concrete admixture is single, making it difficult to effectively improve the freezing resistance and durability of concrete in high-altitude areas.

Method used

Anti-seepage anti-freeze-resistant concrete composite admixtures using a synergistic effect of multiple components, including zeolite powder, sodium nitrite, polyoxyethylene ether, sodium dodecyl benzene sulfonate, polycarboxylic acid water reducer, modified pulverized coal Ash and modified nanocellulose are synthesized by ball milling and high-speed stirring.

Benefits of technology

It significantly improves the frost resistance, seepage and crack resistance of concrete, extends the service life of concrete in high cold environments, and improves the overall density of cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a composite admixture for anti-seepage and antifreeze concrete suitable for alpine areas and a preparation method thereof, and belongs to the technical field of concrete admixtures. It is made of the following raw materials in parts by weight: 10-20 parts of zeolite powder, 1-3 parts of sodium nitrite, 3-5 parts of polyoxyethylene ether, 0.2-0.5 parts of sodium dodecylbenzene sulfonate, 5-8 parts of polycarboxylic acid water reducer, 20-30 parts of modified fly ash, 1-2 parts of modified nanocellulose, and 50-80 parts of water. In the admixture, the antifreeze property of concrete can be significantly improved by the synergistic effect of multiple components, while improving the overall density of cement, significantly improving the anti-seepage and anti-cracking performance of concrete, and having good market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete admixtures, and particularly relates to an anti-seepage and anti-freeze concrete composite admixture suitable for high-cold areas and a preparation method thereof. Background Art

[0002] Concrete is an important material widely used in construction and infrastructure projects. Its composition mainly includes cement, coarse and fine aggregates, concrete admixtures and water. The advantages of concrete are high compressive strength, low cost and excellent performance, but it also has disadvantages such as low tensile strength, poor crack resistance and low toughness, which limit its potential development. Moreover, due to the influence of the service environment, concrete will inevitably suffer from chemical erosion, load damage, freeze-thaw damage and other damages. Freeze-thaw damage is the most common type of damage to concrete. Especially in northern my country, concrete buildings are in a cold environment for a long time, and their freeze-thaw damage is more serious. Therefore, improving the durability of concrete structures, especially anti-freeze durability, has become a key and difficult problem in the research of infrastructure in high-altitude cold areas. Concrete admixtures, as an important part of modern concrete technology, play a key role. These admixtures are precisely formulated chemical or physical additives. Their introduction can not only change the properties of concrete, but also meet different engineering requirements. Antifreeze concrete admixtures can effectively improve the freeze-thaw resistance of concrete and become an application hotspot in the field of concrete admixtures.

[0003] At present, there are many kinds of antifreeze concrete admixtures. Generally, some special properties of substances are added to the concrete to improve its antifreeze properties. However, the existing antifreeze admixtures have relatively simple ingredients, and the effect of improving the concrete performance after being added to the concrete is relatively simple. If the admixture with antifreeze effect can be coordinated with the admixture with other properties to improve the performance of concrete from different aspects, it can greatly expand the market prospects of concrete. Summary of the invention

[0004] The invention provides an anti-seepage and anti-freezing concrete composite admixture suitable for alpine areas. The synergistic effect of multiple components in the admixture can significantly improve the anti-freezing property of concrete, while increasing the overall density of cement and significantly improving the anti-seepage and anti-cracking performance of concrete.

[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0006] A composite admixture for anti-seepage and antifreeze concrete suitable for alpine areas is prepared from the following raw materials in parts by weight: 10-20 parts of zeolite powder, 1-3 parts of sodium nitrite, 3-5 parts of polyoxyethylene ether, 0.2-0.5 parts of sodium dodecylbenzene sulfonate, 5-8 parts of polycarboxylic acid water reducer, 20-30 parts of modified fly ash, 1-2 parts of modified nanocellulose, and 50-80 parts of water.

[0007] Preferably, the modified fly ash is prepared by the following method:

[0008] (1) Fly ash and 20% hydrochloric acid are mixed according to the mass ratio, and then stirred in a water bath at 100°C for 3 hours, cooled to room temperature, filtered, and the fly ash is repeatedly washed until the filtrate is neutral. The fly ash obtained by filtration is then vacuum dried at 100°C for 8 hours, cooled to room temperature, and ground into fine fly ash powder;

[0009] (2) The fly ash fine powder obtained in step (1) was mixed evenly with a 10% mass concentration NaOH solution according to the solid-liquid ratio, and then microwaved at 650 W and 65° C. for 15 min. After cooling to room temperature, the solid obtained by filtration was dried in a vacuum drying oven at 100° C. for 8 h to obtain modified fly ash.

[0010] Preferably, in step (1), the mass ratio of fly ash to hydrochloric acid is 1:10.

[0011] Preferably, in step (2), the solid-to-liquid mass ratio of the fly ash fine powder to the NaOH solution is 1:10.

[0012] Preferably, the modified nanocellulose is prepared by the following method:

[0013] 1) Wash the plant straw and boil it in boiling water for 2 hours, then dry it to constant weight and grind it to obtain straw powder;

[0014] 2) Add the straw powder to a 5% NaOH solution, reflux at 85°C for 2 h, and filter under reduced pressure after the reaction. Wash the filter cake with deionized water until it is neutral, dry and grind to obtain crude cellulose;

[0015] 3) Take crude cellulose, add it to a sodium sulfide solution with a mass concentration of 2%, adjust the solution pH to 2.5 with acetic acid, reflux at 85°C for 2 hours, and filter under reduced pressure after the reaction. Wash the filter cake with ethanol several times and then with water until it is neutral, dry and grind to obtain cellulose;

[0016] 4) adding the cellulose obtained in step 3) into a hydrochloric acid solution with a mass concentration of 2%, stirring and reacting at a constant temperature of 65° C. for 1 hour, filtering and drying after cooling to obtain nanocellulose;

[0017] 5) Take 0.5 g of graphene oxide and add it to 500 ml of deionized water, ultrasonically disperse it for 2 hours, then add 30 g of NaOH and 25 g of chloroacetic acid and continue ultrasonic treatment for 3 hours, then place the mixture at 30°C and stir to react for 48 hours, filter after the reaction, remove the filtrate, and dry the solid in an oven to obtain carboxylated graphene;

[0018] 6) Take 0.5g of carboxylated graphene, then add 20ml of SOCl2, stir evenly, then add 50ml of N,N-dimethylformamide, ultrasonically treat the mixture for 2h, and then reflux at 70°C for 24h. After the reaction is completed, filter under reduced pressure, wash the residue with deionized water until it is neutral, and dry it in an oven to obtain acyl chloride graphene oxide;

[0019] 7) Take 0.5 g of the acyl chloride graphene oxide obtained in step 6) and 5 ml of 1-allyl-3-methylimidazolium chloride, add them to a test tube, and ultrasonically disperse them for 45 minutes to obtain a mixed solution A; mix 1 g of the nanocellulose obtained in step 4) with 10 ml of 1-allyl-3-methylimidazolium chloride, and react at 50°C with magnetic stirring for 1 hour, then add the mixed solution A, adjust the reaction temperature to 30°C, and continue the reaction for 12-16 hours. After the reaction is completed, add a large amount of deionized water to the reaction solution, ultrasonically treat for 1 hour, and then vacuum filter, repeat the above ultrasonic immersion cleaning and filtration steps 3 times, and finally dry the solid product in an oven for 72 hours to obtain modified nanocellulose.

[0020] Preferably, in step 2), the mass ratio of straw powder to NaOH solution is 1:10.

[0021] Preferably, in step 3), the mass ratio of crude cellulose to sodium sulfide solution is 1:50.

[0022] Preferably, in step 4), the liquid-to-solid ratio of the hydrochloric acid solution to the cellulose is 10 ml:1 g.

[0023] A preparation method of the above-mentioned anti-seepage and antifreeze concrete composite admixture suitable for high-cold areas comprises the following steps: zeolite powder, sodium nitrite, polyoxyethylene ether, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, modified fly ash and water are mixed evenly according to the formula amount, and then the mixture is ground for 30 minutes by a ball mill, and then the modified nanocellulose is added thereto, and the mixture is stirred at a high speed to be evenly mixed to obtain the concrete admixture of the present invention.

[0024] The raw materials and reagents used in the present invention are all purchased from the market. The amount of the anti-seepage and anti-freeze concrete composite admixture prepared by the present invention in concrete is 2%.

[0025] Existing relevant studies have shown that the frost resistance of concrete is closely related to parameters related to the pore structure. The present invention effectively improves the internal structure of concrete through the synergistic effect of multiple components, and significantly improves the anti-seepage and anti-freeze performance of concrete. Among them, sodium dodecylbenzene sulfonate can form stable bubbles in the concrete slurry, produce a lubricating effect in the concrete, and improve the frost resistance and workability of the concrete. The active SiO2 and Al2O3 in the zeolite powder are activated in the high alkaline cement gelling system, which can significantly improve the later compressive strength and tensile strength of the concrete; sodium nitrite acts as an antifreeze agent in synergy with the modified fly ash to improve the freeze-thaw resistance of the concrete; the polycarboxylate water reducer can reduce the water consumption, reduce the water-cement ratio, and then increase the density of the cement paste structure, which is beneficial to the increase of the strength and impermeability of the concrete; and the polycarboxylate water reducer can improve the pore structure inside the concrete after compounding with the modified nanocellulose of the present invention, effectively reduce the number of harmful pores, and thus improve the frost resistance of the concrete; polyoxyethylene ether, as a nonionic surfactant, can well improve the dispersibility of the modified nanocellulose of the present invention, and synergize with other components to achieve efficient anti-seepage and anti-freeze effects; the modified nanocellulose has a larger specific surface area and has a variety of functional groups, has good adsorption capacity, and can effectively adsorb the concrete A variety of harmful heavy metal ions, the products formed after adsorption, uniformly block various pore structures in the concrete, achieve compaction and filling effects, and make the concrete structure more compact; at the same time, due to the combination of the nanocrystalline state of modified nanocellulose and the lamellar network structure characteristics of graphene, the synergistic effect of the two makes the concrete structure more compact, improves the impermeability of concrete and can also increase the mechanical properties of concrete; a large amount of modified fly ash is filled in the pore structure formed by concrete, on the one hand, a large amount of modified fly ash can reduce the absorption of water at the root, thereby reducing the water content of concrete materials and enhancing antifreeze performance; on the other hand, the density of the hardened slurry can be improved, thereby inhibiting the shrinkage cracking of concrete, reducing the number of harmful cracks in concrete and the total area of ​​cracks, preventing harmful ions, mainly chloride ions, from further invading the interior of concrete, avoiding the collapse and explosion of concrete, and improving the durability of concrete. And the modified nanocellulose in the present invention contains graphene oxide components, which can improve the bending and tensile properties of concrete, thereby further improving the performance of concrete and extending the service life of concrete.

[0026] The beneficial effects of the present invention are as follows: the present invention reasonably matches the prepared modified nanocellulose, modified fly ash and other multiple components, and the multiple functional components act synergistically to effectively improve the internal structure of concrete, improve the anti-seepage and anti-freeze-thaw properties of concrete, and improve the durability of concrete in high-cold environments. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0028] Example 1

[0029] A composite admixture for anti-seepage and antifreeze concrete suitable for alpine areas is prepared from the following raw materials in parts by weight: 10 parts of zeolite powder, 1 part of sodium nitrite, 3 parts of polyoxyethylene ether, 0.2 parts of sodium dodecylbenzene sulfonate, 5 parts of polycarboxylic acid water reducer, 20 parts of modified fly ash, 1 part of modified nanocellulose, and 50 parts of water.

[0030] The modified fly ash is prepared by the following method:

[0031] (1) Fly ash and 20% hydrochloric acid were mixed in a mass ratio of 1:10, and then stirred in a water bath at 100°C for 3 hours, cooled to room temperature, filtered, and the fly ash was repeatedly washed until the filtrate was neutral. The filtered fly ash was then vacuum dried at 100°C for 8 hours, cooled to room temperature, and ground into fine fly ash powder;

[0032] (2) The fly ash fine powder obtained in step (1) was mixed evenly with a 10% NaOH solution in a solid-liquid ratio of 1:10, and then microwaved at 650 W and 65° C. for 15 min. After cooling to room temperature, the solid obtained by filtration was dried in a vacuum drying oven at 100° C. for 8 h to obtain modified fly ash.

[0033] The modified nanocellulose is prepared by the following method:

[0034] 1) Wash the plant straw and boil it in boiling water for 2 hours, then dry it to constant weight and grind it to obtain straw powder;

[0035] 2) Add straw powder to a 5% NaOH solution, reflux at 85°C for 2 h, and filter under reduced pressure after the reaction. Wash the filter cake with deionized water until it is neutral, dry and grind to obtain crude cellulose; the mass ratio of straw powder to NaOH solution is 1:10;

[0036] 3) Take crude cellulose, add it to a sodium sulfide solution with a mass concentration of 2%, adjust the solution pH to 2.5 with acetic acid, reflux at 85°C for 2 hours, and filter under reduced pressure after the reaction. Wash the filter cake with ethanol several times and then with water until neutral, dry and grind to obtain cellulose; the mass ratio of crude cellulose to sodium sulfide solution is 1:50;

[0037] 4) adding the cellulose obtained in step 3) into a hydrochloric acid solution with a mass concentration of 2%, stirring and reacting at a constant temperature of 65°C for 1 hour, filtering and drying after cooling to obtain nanocellulose; the liquid-to-solid ratio of the hydrochloric acid solution to the cellulose is 10 ml: 1 g;

[0038] 5) Take 0.5 g of graphene oxide and add it to 500 ml of deionized water, ultrasonically disperse it for 2 hours, then add 30 g of NaOH and 25 g of chloroacetic acid and continue ultrasonic treatment for 3 hours, then place the mixture at 30°C and stir to react for 48 hours, filter after the reaction, remove the filtrate, and dry the solid in an oven to obtain carboxylated graphene;

[0039] 6) Take 0.5g of carboxylated graphene, then add 20ml of SOCl2, stir evenly, then add 50ml of N,N-dimethylformamide, ultrasonically treat the mixture for 2h, and then reflux at 70°C for 24h. After the reaction is completed, filter under reduced pressure, wash the residue with deionized water until it is neutral, and dry it in an oven to obtain acyl chloride graphene oxide;

[0040] 7) Take 0.5 g of the acyl chloride graphene oxide obtained in step 6) and 5 ml of 1-allyl-3-methylimidazolium chloride, add them to a test tube, and ultrasonically disperse them for 45 minutes to obtain a mixed solution A; mix 1 g of the nanocellulose obtained in step 4) with 10 ml of 1-allyl-3-methylimidazolium chloride, and react at 50°C with magnetic stirring for 1 hour, then add the mixed solution A, adjust the reaction temperature to 30°C, and continue the reaction for 12-16 hours. After the reaction is completed, add a large amount of deionized water to the reaction solution, ultrasonically treat for 1 hour, and then vacuum filter, repeat the above ultrasonic immersion cleaning and filtration steps 3 times, and finally dry the solid product in an oven for 72 hours to obtain modified nanocellulose.

[0041] The preparation method of the above-mentioned anti-seepage and anti-freeze concrete composite admixture suitable for high-cold areas comprises the following steps: zeolite powder, sodium nitrite, polyoxyethylene ether, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, modified fly ash and water are mixed evenly according to the formula amount, and then the mixture is ground for 30 minutes by a ball mill, and then the modified nanocellulose is added thereto, and the mixture is stirred at a high speed to be evenly mixed to obtain the concrete admixture of the present invention.

[0042] Example 2

[0043] A composite admixture for anti-seepage and antifreeze concrete suitable for alpine areas is prepared from the following raw materials in parts by weight: 20 parts of zeolite powder, 3 parts of sodium nitrite, 5 parts of polyoxyethylene ether, 0.5 parts of sodium dodecylbenzene sulfonate, 8 parts of polycarboxylic acid water reducer, 30 parts of modified fly ash, 2 parts of modified nanocellulose, and 80 parts of water.

[0044] The modified fly ash is prepared by the following method:

[0045] (1) Fly ash and 20% hydrochloric acid were mixed in a mass ratio of 1:10, and then stirred in a water bath at 100°C for 3 hours, cooled to room temperature, filtered, and the fly ash was repeatedly washed until the filtrate was neutral. The filtered fly ash was then vacuum dried at 100°C for 8 hours, cooled to room temperature, and ground into fine fly ash powder;

[0046] (2) The fly ash fine powder obtained in step (1) was mixed evenly with a 10% NaOH solution in a solid-liquid ratio of 1:10, and then microwaved at 650 W and 65° C. for 15 min. After cooling to room temperature, the solid obtained by filtration was dried in a vacuum drying oven at 100° C. for 8 h to obtain modified fly ash.

[0047] The modified nanocellulose is prepared by the following method:

[0048] 1) Wash the plant straw and boil it in boiling water for 2 hours, then dry it to constant weight and grind it to obtain straw powder;

[0049] 2) Add straw powder to a 5% NaOH solution, reflux at 85°C for 2 h, and filter under reduced pressure after the reaction. Wash the filter cake with deionized water until it is neutral, dry and grind to obtain crude cellulose; the mass ratio of straw powder to NaOH solution is 1:10;

[0050] 3) Take crude cellulose, add it to a sodium sulfide solution with a mass concentration of 2%, adjust the solution pH to 2.5 with acetic acid, reflux at 85°C for 2 hours, and filter under reduced pressure after the reaction. Wash the filter cake with ethanol several times and then with water until neutral, dry and grind to obtain cellulose; the mass ratio of crude cellulose to sodium sulfide solution is 1:50;

[0051] 4) adding the cellulose obtained in step 3) into a hydrochloric acid solution with a mass concentration of 2%, stirring and reacting at a constant temperature of 65°C for 1 hour, filtering and drying after cooling to obtain nanocellulose; the liquid-to-solid ratio of the hydrochloric acid solution to the cellulose is 10 ml: 1 g;

[0052] 5) Take 0.5 g of graphene oxide and add it to 500 ml of deionized water, ultrasonically disperse it for 2 hours, then add 30 g of NaOH and 25 g of chloroacetic acid and continue ultrasonic treatment for 3 hours, then place the mixture at 30°C and stir to react for 48 hours, filter after the reaction, remove the filtrate, and dry the solid in an oven to obtain carboxylated graphene;

[0053] 6) Take 0.5g of carboxylated graphene, then add 20ml of SOCl2, stir evenly, then add 50ml of N,N-dimethylformamide, ultrasonically treat the mixture for 2h, and then reflux at 70°C for 24h. After the reaction is completed, filter under reduced pressure, wash the residue with deionized water until it is neutral, and dry it in an oven to obtain acyl chloride graphene oxide;

[0054] 7) Take 0.5 g of the acyl chloride graphene oxide obtained in step 6) and 5 ml of 1-allyl-3-methylimidazolium chloride, add them to a test tube, and ultrasonically disperse them for 45 minutes to obtain a mixed solution A; mix 1 g of the nanocellulose obtained in step 4) with 10 ml of 1-allyl-3-methylimidazolium chloride, and react at 50°C with magnetic stirring for 1 hour, then add the mixed solution A, adjust the reaction temperature to 30°C, and continue the reaction for 12-16 hours. After the reaction is completed, add a large amount of deionized water to the reaction solution, ultrasonically treat for 1 hour, and then vacuum filter, repeat the above ultrasonic immersion cleaning and filtration steps 3 times, and finally dry the solid product in an oven for 72 hours to obtain modified nanocellulose.

[0055] The preparation method of the above-mentioned anti-seepage and anti-freeze concrete composite admixture suitable for high-cold areas comprises the following steps: zeolite powder, sodium nitrite, polyoxyethylene ether, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, modified fly ash and water are mixed evenly according to the formula amount, and then the mixture is ground for 30 minutes by a ball mill, and then the modified nanocellulose is added thereto, and the mixture is stirred at a high speed to be evenly mixed to obtain the concrete admixture of the present invention.

[0056] Example 3

[0057] A composite admixture for anti-seepage and antifreeze concrete suitable for alpine areas is prepared from the following raw materials in parts by weight: 15 parts of zeolite powder, 2 parts of sodium nitrite, 4 parts of polyoxyethylene ether, 0.4 parts of sodium dodecylbenzene sulfonate, 6 parts of polycarboxylic acid water reducer, 25 parts of modified fly ash, 1.5 parts of modified nanocellulose, and 70 parts of water.

[0058] The modified fly ash is prepared by the following method:

[0059] (1) Fly ash and 20% hydrochloric acid were mixed in a mass ratio of 1:10, and then stirred in a water bath at 100°C for 3 hours, cooled to room temperature, filtered, and the fly ash was repeatedly washed until the filtrate was neutral. The filtered fly ash was then vacuum dried at 100°C for 8 hours, cooled to room temperature, and ground into fine fly ash powder;

[0060] (2) The fly ash fine powder obtained in step (1) was mixed evenly with a 10% NaOH solution in a solid-liquid ratio of 1:10, and then microwaved at 650 W and 65° C. for 15 min. After cooling to room temperature, the solid obtained by filtration was dried in a vacuum drying oven at 100° C. for 8 h to obtain modified fly ash.

[0061] The modified nanocellulose is prepared by the following method:

[0062] 1) Wash the plant straw and boil it in boiling water for 2 hours, then dry it to constant weight and grind it to obtain straw powder;

[0063] 2) Add straw powder to a 5% NaOH solution, reflux at 85°C for 2 h, and filter under reduced pressure after the reaction. Wash the filter cake with deionized water until it is neutral, dry and grind to obtain crude cellulose; the mass ratio of straw powder to NaOH solution is 1:10;

[0064] 3) Take crude cellulose, add it to a sodium sulfide solution with a mass concentration of 2%, adjust the solution pH to 2.5 with acetic acid, reflux at 85°C for 2 hours, and filter under reduced pressure after the reaction. Wash the filter cake with ethanol several times and then with water until neutral, dry and grind to obtain cellulose; the mass ratio of crude cellulose to sodium sulfide solution is 1:50;

[0065] 4) adding the cellulose obtained in step 3) into a hydrochloric acid solution with a mass concentration of 2%, stirring and reacting at a constant temperature of 65°C for 1 hour, filtering and drying after cooling to obtain nanocellulose; the liquid-to-solid ratio of the hydrochloric acid solution to the cellulose is 10 ml: 1 g;

[0066] 5) Take 0.5 g of graphene oxide and add it to 500 ml of deionized water, ultrasonically disperse it for 2 hours, then add 30 g of NaOH and 25 g of chloroacetic acid and continue ultrasonic treatment for 3 hours, then place the mixture at 30°C and stir to react for 48 hours, filter after the reaction, remove the filtrate, and dry the solid in an oven to obtain carboxylated graphene;

[0067] 6) Take 0.5g of carboxylated graphene, then add 20ml of SOCl2, stir evenly, then add 50ml of N,N-dimethylformamide, ultrasonically treat the mixture for 2h, and then reflux at 70°C for 24h. After the reaction is completed, filter under reduced pressure, wash the residue with deionized water until it is neutral, and dry it in an oven to obtain acyl chloride graphene oxide;

[0068] 7) Take 0.5 g of the acyl chloride graphene oxide obtained in step 6) and 5 ml of 1-allyl-3-methylimidazolium chloride, add them to a test tube, and ultrasonically disperse them for 45 minutes to obtain a mixed solution A; mix 1 g of the nanocellulose obtained in step 4) with 10 ml of 1-allyl-3-methylimidazolium chloride, and react at 50°C with magnetic stirring for 1 hour, then add the mixed solution A, adjust the reaction temperature to 30°C, and continue the reaction for 12-16 hours. After the reaction is completed, add a large amount of deionized water to the reaction solution, ultrasonically treat for 1 hour, and then vacuum filter, repeat the above ultrasonic immersion cleaning and filtration steps 3 times, and finally dry the solid product in an oven for 72 hours to obtain modified nanocellulose.

[0069] The preparation method of the above-mentioned anti-seepage and anti-freeze concrete composite admixture suitable for high-cold areas comprises the following steps: zeolite powder, sodium nitrite, polyoxyethylene ether, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, modified fly ash and water are mixed evenly according to the formula amount, and then the mixture is ground for 30 minutes by a ball mill, and then the modified nanocellulose is added thereto, and the mixture is stirred at a high speed to be evenly mixed to obtain the concrete admixture of the present invention.

[0070] Comparative Example 1

[0071] A composite admixture for anti-seepage and antifreeze concrete suitable for alpine areas is prepared from the following raw materials in parts by weight: 15 parts of zeolite powder, 2 parts of sodium nitrite, 4 parts of polyoxyethylene ether, 0.4 parts of sodium dodecylbenzene sulfonate, 6 parts of polycarboxylic acid water reducer, 25 parts of fly ash, 1.5 parts of modified nanocellulose, and 70 parts of water.

[0072] The modified nanocellulose is prepared by the following method:

[0073] 1) Wash the plant straw and boil it in boiling water for 2 hours, then dry it to constant weight and grind it to obtain straw powder;

[0074] 2) Add straw powder to a 5% NaOH solution, reflux at 85°C for 2 h, and filter under reduced pressure after the reaction. Wash the filter cake with deionized water until it is neutral, dry and grind to obtain crude cellulose; the mass ratio of straw powder to NaOH solution is 1:10;

[0075] 3) Take crude cellulose, add it to a sodium sulfide solution with a mass concentration of 2%, adjust the solution pH to 2.5 with acetic acid, reflux at 85°C for 2 hours, and filter under reduced pressure after the reaction. Wash the filter cake with ethanol several times and then with water until neutral, dry and grind to obtain cellulose; the mass ratio of crude cellulose to sodium sulfide solution is 1:50;

[0076] 4) adding the cellulose obtained in step 3) into a hydrochloric acid solution with a mass concentration of 2%, stirring and reacting at a constant temperature of 65°C for 1 hour, filtering and drying after cooling to obtain nanocellulose; the liquid-to-solid ratio of the hydrochloric acid solution to the cellulose is 10ml:1g;

[0077] 5) Take 0.5 g of graphene oxide and add it to 500 ml of deionized water, ultrasonically disperse it for 2 hours, then add 30 g of NaOH and 25 g of chloroacetic acid and continue ultrasonic treatment for 3 hours, then place the mixture at 30°C and stir to react for 48 hours, filter after the reaction, remove the filtrate, and dry the solid in an oven to obtain carboxylated graphene;

[0078] 6) Take 0.5g of carboxylated graphene, then add 20ml of SOCl2, stir evenly, then add 50ml of N,N-dimethylformamide, ultrasonically treat the mixture for 2h, and then reflux at 70°C for 24h. After the reaction is completed, filter under reduced pressure, wash the residue with deionized water until it is neutral, and dry it in an oven to obtain acyl chloride graphene oxide;

[0079] 7) Take 0.5 g of the acyl chloride graphene oxide obtained in step 6) and 5 ml of 1-allyl-3-methylimidazolium chloride, add them to a test tube, and ultrasonically disperse them for 45 minutes to obtain a mixed solution A; mix 1 g of the nanocellulose obtained in step 4) with 10 ml of 1-allyl-3-methylimidazolium chloride, and react at 50°C with magnetic stirring for 1 hour, then add the mixed solution A, adjust the reaction temperature to 30°C, and continue the reaction for 12-16 hours. After the reaction is completed, add a large amount of deionized water to the reaction solution, ultrasonically treat for 1 hour, and then vacuum filter, repeat the above ultrasonic immersion cleaning and filtration steps 3 times, and finally dry the solid product in an oven for 72 hours to obtain modified nanocellulose.

[0080] The preparation method of the above-mentioned anti-seepage and anti-freeze concrete composite admixture suitable for high-cold areas comprises the following steps: zeolite powder, sodium nitrite, polyoxyethylene ether, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, fly ash and water are mixed evenly according to the formula amount, and then the mixture is ground for 30 minutes by a ball mill, and the modified nanocellulose is added thereto, and the mixture is stirred at a high speed to be evenly mixed to obtain the concrete admixture of the present invention.

[0081] This comparative example is basically the same as Example 3, the only difference being that ordinary unmodified fly ash is used instead of modified fly ash.

[0082] Comparative Example 2

[0083] A composite admixture for anti-seepage and anti-freezing concrete suitable for alpine areas, the formula composition and preparation method of which are basically the same as those of Example 3, the only difference being that modified fly ash and its corresponding preparation steps are not included.

[0084] Comparative Example 3

[0085] A composite admixture for anti-seepage and anti-freezing concrete suitable for alpine areas, the formula composition and preparation method of which are basically the same as those of Example 3, the only difference being that there is no modified nanocellulose and its corresponding preparation steps.

[0086] Comparative Example 4

[0087] A composite admixture for anti-seepage and anti-freezing concrete suitable for alpine areas, the formula composition and preparation method of which are basically the same as those of Example 3, the only difference being that there is no polycarboxylate water reducer.

[0088] Comparative Example 5

[0089] A composite admixture for anti-seepage and anti-freezing concrete suitable for alpine areas, the formula composition and preparation method of which are basically the same as those of Example 3, the only difference being that sodium nitrite is not contained.

[0090] Performance Testing

[0091] Taking C30 concrete as a benchmark, the anti-seepage and anti-freeze concrete composite admixtures suitable for high-cold areas obtained in Examples 1-3 and Comparative Examples 1-5 were added to the concrete at an amount of 2% of the weight of the concrete material, and then the concrete samples were subjected to performance tests. The workability of the concrete was tested according to GB / T 50080-2011 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the strength of the concrete was tested according to GB / T 50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the anti-seepage performance of the concrete specimens with a curing age of 28 days was measured according to the chloride ion penetration method in GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and the anti-cracking performance of the concrete under restraint was measured using a flat concrete crack resistance tester. The concrete freeze-thaw test was carried out according to the quick freezing method in the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2009), and the mass loss rate, compressive strength and chloride ion diffusion coefficient of the concrete samples after 200 freeze-thaw cycles were tested. The performance test results are shown in Table 1 below.

[0092] Table 1 Performance test results

[0093]

[0094] From the data in Table 1 above, it can be seen that after the composite concrete admixture of the present invention is added to concrete for use, the synergistic effect of multiple components can significantly improve the frost resistance of concrete, extend the construction period of concrete under high-cold and complex environmental conditions, and is simple, practical, environmentally friendly and harmless, with important practical significance and engineering application value. At the same time, the admixture of the present invention can also improve the overall density of cement, significantly improve the anti-seepage and anti-cracking performance and mechanical properties of concrete, and improve the durability of concrete.

[0095] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A composite admixture for anti-seepage and anti-freezing concrete suitable for high-cold areas, characterized in that: It is made of the following raw materials in parts by weight: 10-20 parts of zeolite powder, 1-3 parts of sodium nitrite, 3-5 parts of polyoxyethylene ether, 0.2-0.5 parts of sodium dodecylbenzene sulfonate, 5-8 parts of polycarboxylic acid water reducer, 20-30 parts of modified fly ash, 1-2 parts of modified nanocellulose, and 50-80 parts of water; The modified fly ash is prepared by the following method: (1) Fly ash and 20% hydrochloric acid are mixed according to the mass ratio, and then stirred in a water bath at 100°C for 3 hours, cooled to room temperature, filtered, and the fly ash is repeatedly washed until the filtrate is neutral. The fly ash obtained by filtration is then vacuum dried at 100°C for 8 hours, cooled to room temperature, and ground into fine fly ash powder; (2) The fly ash fine powder obtained in step (1) was mixed evenly with a 10% mass concentration NaOH solution according to the solid-liquid ratio, and then microwaved at 650W and 65°C for 15 min. After cooling to room temperature, the solid obtained by filtration was dried in a vacuum drying oven at 100°C for 8 h to obtain modified fly ash; The modified nanocellulose is prepared by the following method: 1) Wash the plant straw and boil it in boiling water for 2 hours, then dry it to constant weight and grind it to obtain straw powder; 2) Add the straw powder to a 5% NaOH solution, reflux at 85°C for 2 h, and filter under reduced pressure after the reaction. Wash the filter cake with deionized water until it is neutral, dry and grind to obtain crude cellulose; 3) Take crude cellulose, add it to a sodium sulfide solution with a mass concentration of 2%, adjust the solution pH to 2.5 with acetic acid, reflux at 85°C for 2 hours, and filter under reduced pressure after the reaction. Wash the filter cake with ethanol several times and then with water until it is neutral, dry and grind to obtain cellulose; 4) adding the cellulose obtained in step 3) into a hydrochloric acid solution with a mass concentration of 2%, stirring and reacting at a constant temperature of 65° C. for 1 hour, filtering and drying after cooling to obtain nanocellulose; 5) Take 0.5 g of graphene oxide and add it to 500 ml of deionized water, ultrasonically disperse it for 2 hours, then add 30 g of NaOH and 25 g of chloroacetic acid and continue ultrasonic treatment for 3 hours, then place the mixture at 30°C and stir to react for 48 hours, filter after the reaction, remove the filtrate, and dry the solid in an oven to obtain carboxylated graphene; 6) Take 0.5g of carboxylated graphene, then add 20ml of SOCl2, stir evenly, then add 50ml of N,N-dimethylformamide, ultrasonically treat the mixture for 2h, and then reflux at 70°C for 24h. After the reaction is completed, filter under reduced pressure, wash the residue with deionized water until it is neutral, and dry it in an oven to obtain acyl chloride graphene oxide; 7) Take 0.5 g of the acyl chloride graphene oxide obtained in step 6) and 5 ml of 1-allyl-3-methylimidazolium chloride, add them to a test tube, and ultrasonically disperse them for 45 minutes to obtain a mixed solution A; mix 1 g of the nanocellulose obtained in step 4) with 10 ml of 1-allyl-3-methylimidazolium chloride, and react at 50°C with magnetic stirring for 1 hour, then add the mixed solution A, adjust the reaction temperature to 30°C, and continue the reaction for 12-16 hours. After the reaction is completed, add a large amount of deionized water to the reaction solution, ultrasonically treat for 1 hour, and then vacuum filter, repeat the above ultrasonic immersion cleaning and filtration steps 3 times, and finally dry the solid product in an oven for 72 hours to obtain modified nanocellulose.

2. The anti-seepage and anti-freeze concrete composite admixture suitable for high-cold areas according to claim 1, characterized in that: In the step (1), the mass ratio of fly ash to hydrochloric acid is 1:

10.

3. The anti-seepage and anti-freezing concrete composite admixture suitable for high-cold areas according to claim 1, characterized in that: In the step (2), the solid-liquid mass ratio of the fly ash fine powder to the NaOH solution is 1:

10.

4. The anti-seepage and anti-freezing concrete composite admixture suitable for high-cold areas according to claim 1, characterized in that: In the step 2), the mass ratio of the straw powder to the NaOH solution is 1:

10.

5. The anti-seepage and anti-freezing concrete composite admixture suitable for high-cold areas according to claim 1, characterized in that: In step 3), the mass ratio of crude cellulose to sodium sulfide solution is 1:

50.

6. The anti-seepage and anti-freezing concrete composite admixture suitable for high-cold areas according to claim 1, characterized in that: In step 4), the liquid-to-solid ratio of the hydrochloric acid solution to the cellulose is 10 ml:1 g.

7. A method for preparing the anti-seepage and anti-freeze concrete composite admixture suitable for high-cold areas according to any one of claims 1 to 6, characterized in that: The following steps are involved: Zeolite powder, sodium nitrite, polyoxyethylene ether, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, modified fly ash and water are mixed evenly according to the formula amount, and then the mixture is ground by a ball mill for 30 minutes, and then the modified nanocellulose is added thereto, and the mixture is stirred at a high speed to be evenly mixed to obtain an anti-seepage and anti-freeze concrete composite admixture suitable for high-cold areas.

Citation Information

Patent Citations

  • Preparation method of modified fly ash adsorbent for adsorbing VOCs

    CN110773114A

  • Anti-freezing concrete and preparation method thereof

    CN112979241A

  • Mass concrete for tunnel and preparation method thereof

    CN117486558A